Effects of Charged Cholesterol Derivatives on Aβ40 Amyloid Formation - Elbassal, Esmail A. (J Phys Chem B, 2015)
Understanding of the mechanistic progess of Amyloid-β peptide (Aβ) aggregation is critical for elucidating the underlying pathogenesis of Alzheimer’s disease (AD). Herein, we report for the first time the effects of two cholesterol derivatives, negatively charged cholesterol sulfate (cholesterol-SO(4)) and positively charged 3β-[N-(dimethylaminoethane)carbamoyl]-cholesterol (DC-cholesterol), on the fibrillization of Aβ40. Our results demonstrate that both of the nonvesicle forms of cholesterol-SO(4) and DC-cholesterol moderately accelerate the aggregation rate of Aβ40. This effect is similar to that observed for unmodified cholesterol, indicating the importance of hydrophobic interactions in binding of Aβ40 to these steroid molecules. Furthermore, we show that the vesicles formed at higher concentrations of anionic cholesterol-SO(4) facilitate Aβ40 aggregation rate markedly. In contrast, the cationic DC-cholesterol vesicles show the ability to inhibit Aβ40 fibril formation under appropriate experimental conditions. The results suggest that the electrostatic interactions between Aβ40 and the charged vesicles can be of great importance in regulating Aβ40-vesicle interaction. Our results also indicate that the structural properties of the aggregates of the cholesterol derivatives, including the surface charge and the size of the vesicles, are critical in regulating the effects of these vesicles on Aβ40 aggregation kinetics.